Implementasi Kegiatan Religius dalam Meningkatkan Akhlakul Karimah Siswa di Madrasah Aliyah Qodiriyah Harjowinangun Dempet Demak - Taufikin, Taufikin; Falah, Ahmad (LP2M IAIN kUDUS, 2020)
Akhlakul Karimah (noble character) cannot be formed on its own without coaching. Coaching can be formed through religious activities. This reseacrh aims to analysis: (1) religious activities implemented in improving morality in the Madrasah Aliyah (MA) Qodiriyah Harjowinangun Dempet Demak in 2019 and (2) What are the implications of the implementation of religious activities in Madrasah Aliyah (MA) Qodiriyah Harjowinangun Dempet Demak and (2) What are the implications of the implementation of religious activities in Madrasah Aliyah (MA) Qodiriyah Harjowinangun Dempet Demak. This research is a type of field research using a qualitative approach. Data collection techniques carried out by (1) interviews, (2) observation and (3) documentation. Data were analysis with an interactive model consisting of data collection, data reduction, data display and conclussion. The results of this study indicate that: (1) the implementation of religious activities in improving morality in the MA Qodiriya consists of Daily, Selapanan, and insidentally. Namely istighotsah ahad kliwon with reading manaqib, teacher fasting on Monday dan Thursday, dzuhur in congregation, teaching in a sacred state (wudlu), guardian pilgrimage, Qiyamullail and khotmil Qur’an. (2) Implications of implementing activities for religius; first, students have a more consistent iman and taqwa than before, second, have a habit of amal saleh, third are accustomed to acting in accordance with noble character.